2015
DOI: 10.1111/tmi.12434
|View full text |Cite
|
Sign up to set email alerts
|

Self‐transfer and mortality amongst adults lost to follow‐up in ART programmes in low‐ and middle‐income countries: systematic review and meta‐analysis

Abstract: Abstractobjective To ascertain estimates of adult patients, recorded as lost to follow-up (LTFU) within antiretroviral treatment (ART) programmes, who have self-transferred care, died or truly stopped ART in low-and middle-income countries.methods PubMed, EMBASE, Web of Science, Science Direct, LILACS, IndMed and AIM databases (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) and IAS/AIDS conference abstracts (2011)(2012)(2013) were searched for tracing studies reporting the proportion of trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
102
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 55 publications
5
102
4
Order By: Relevance
“…Although national standard operating procedures required a routine phone call three days after a missed appointment in order to re-engage women into care or ascertain the outcome, 60% of women could not be contacted due to incorrect contact details (phone numbers did not exist, were unreachable, or somebody else answered the phone). Weak ascertainment of ART outcomes and suboptimal implementation of physical defaulter tracing activities may have inflated attrition rates [48, 49]. Third, this observational study was likely affected by temporal trends such as patient and community mobilization as well as countrywide adoption and scale-up of PMTCTB+ in the second half of 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Although national standard operating procedures required a routine phone call three days after a missed appointment in order to re-engage women into care or ascertain the outcome, 60% of women could not be contacted due to incorrect contact details (phone numbers did not exist, were unreachable, or somebody else answered the phone). Weak ascertainment of ART outcomes and suboptimal implementation of physical defaulter tracing activities may have inflated attrition rates [48, 49]. Third, this observational study was likely affected by temporal trends such as patient and community mobilization as well as countrywide adoption and scale-up of PMTCTB+ in the second half of 2014.…”
Section: Discussionmentioning
confidence: 99%
“…This mortality rate could be an underestimate given recent findings from two reviews suggesting that more than one-third of those lost to follow-up in sub-Saharan Africa die soon afterward [33,34]. However, the generalizability of the proportion of lost to follow-up patients that die in Myanmar is uncertain, given that most data in the above-mentioned reviews were from sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Whilst cohorts that started ART prior to 2008 in Khayelitsha were reported to have higher 6-month retention outcomes, 23 a recent study reporting on MSF cohorts has shown higher losses to care in more recently initiated cohorts, with the 2011 cohort retaining 85.5% (95% CI 84.5% -86.4%) at this time point. 22 It is worth noting that it may not be appropriate to compare retention reported in older versus more recently initiated cohorts; this point is due to increasing unaccounted-for self-transfers hidden within the lost to follow-up (LTFU) outcome 24 and a bias towards better retention outcomes in older cohorts introduced by longer follow-up times, which allow transient treatment interrupters to return to care. 25 It took less than a week for patients to initiate ART from starting ART preparation counselling.…”
Section: Discussionmentioning
confidence: 99%